ChemInform Abstract: Organocatalyzed Asymmetric Alkylation of Stable Aryl or Heteroaryl(3‐indolyl)methylium o‐Benzenedisulfonimides. Issue 49 (December 2015) - Armenise, Nicola; Dughera, Stefano; Gualandi, Andrea; Mengozzi, Luca; Barbero, Margherita; Cozzi, Pier Giorgio
Abstract: The title reaction, established for a way to diarylmethane or diarylethane compounds, is investigated for substrates of type (I) with a strong Broensted acid as counterion and the analogue (VII) bearing a BF4 counterion.